The Role of Healthcare Workers in HPV Prevention: Insights and Implications for Public Health in Gujarat - Shrivastava, Gunjan; Sadhu, Ripal; Sinh Gohil, Disha Kamaljit; Roshiya, Kalpesh Dhanji; Patadia, HemantKumar (Journal of Neonatal Surgery, 2025)
Human papillomavirus (HPV) infection and its related health effects, including cervical cancer. HCWs play a crucial role in raising awareness, busting myths, supporting the use of HPV vaccination and screening services since they are reliable sources of health information. Implementing public health programmes requires their active participation, particularly in places where access to preventive care or knowledge is restricted. This abstract examines important aspects of health care workers' duties, such as patient education, vaccine advocacy, and involvement in early detection initiatives. It also looks at the difficulties they encounter, like cultural barriers, vaccine hesitancy, and knowledge gaps, and provides recommendations for practices and policies meant to increase their ability. Improving HCWs' roles through focused training, encouraging regulations, and interprofessional cooperation will greatly increase efforts to prevent HPV and lower the number of diseases linked to HPV worldwide.